2018
DOI: 10.1097/md.0000000000010092
|View full text |Cite
|
Sign up to set email alerts
|

Observational study pelvic ultrasound a useful tool in the diagnosis and differentiation of precocious puberty in Chinese girls

Abstract: Rapid and noninvasive diagnosis on and differentiation between normal, central precocious puberty (CPP), and isolated precocious puberty (IPP) is imperative before a decision can be made with gonadotropin-releasing hormone (GnRH) agonist treatment. Our study aims to evaluate such a role by pelvic ultrasound.We consecutively enrolled 84 cases of IPP (59 with premature thelarche/ pubarche and 25 with premature menarche), 47 CPP, and 177 age-matched normal controls. The IPP and CPP were diagnosed by clinical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
6
16
0
Order By: Relevance
“…The uterine and ovarian volume was calculated by the formula: Volume = length × anteroposterior diameter × transverse diameter × 0.5233. There was no significant difference in the size of the bilateral ovaries (Wen et al, 2018). Therefore, the average of the bilateral ovaries was calculated for statistical analysis.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…The uterine and ovarian volume was calculated by the formula: Volume = length × anteroposterior diameter × transverse diameter × 0.5233. There was no significant difference in the size of the bilateral ovaries (Wen et al, 2018). Therefore, the average of the bilateral ovaries was calculated for statistical analysis.…”
Section: Methodsmentioning
confidence: 83%
“…According to our study, with a cutoff value of 1.01 cm 3 in the volume of uterine body to diagnose ICPP, the sensitivity and specificity are 91.6 and 68.7%, respectively. Wen et al reported endometrial thickness was the best parameter for distinguishing CPP from normal girls in the 8–10 year interval, where a cutoff of 0.26 cm had a sensitivity of 76.92% and specificity of 100% (Wen et al, 2018). The cutoff values have a certain reference value for the diagnosis of CPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that basal luteinizing hormone (LH) levels and pelvic ultrasound findings are important predictors of central precocious puberty. 6 8 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that basal luteinizing hormone (LH) levels and pelvic ultrasound findings are important predictors of central precocious puberty. [6][7][8] Therefore, we conducted this study to establish an ICPP diagnostic model with transrectal pelvic ultrasound and basal gonadotropin as variables, and to evaluate the diagnostic efficacy of this model.…”
Section: Introductionmentioning
confidence: 99%